Determining the relationship between cytokeratin expression and prognostic factors in human gastric cancer - Zheng, Xiaojia; Chen, Pingping; Liu, Yang; Wang, Bin; Liu, Qiquan (Cellular and Molecular Biology, 2022)
Determining the prognosis of gastric cancer is the most crucial step in the treatment process. Cytokeratins are intermediate filaments found in the intracellular structure of epithelial tissues. Recent researches have focused on determining the relationship between the expression of cytokeratins and the degree and prognosis of tumors. This study aimed to investigate the relationship between the incidence of cytokeratin-20 and cytokeratin-7 in patients with gastric carcinoma with factors influencing the prognosis. In this regard, the study was conducted cross-sectional. The expression of cytokeratin-20 and cytokeratin-7 was evaluated on 50 gastric adenocarcinoma specimens with different degrees of differentiation by the immunohistochemical method. We determined the relationship between the incidence of cytokeratin-20 and cytokeratin-7 with factors affecting the prognosis of patients, including the degree of differentiation of gastric cancer tissue, lymph node involvement, and the depth of tumor invasion. Data were statistically analyzed by Chi-square and Spearman tests. The results showed a statistically inverse relationship between the incidence of cytokeratin-20 and cytokeratin-7 with the degree of tissue differentiation and lymph node involvement in gastric cancer. Although there was a statistically significant relationship between the incidence of tissue invasion in gastric cancer and the incidence of cytokeratin-7, there was no association between the incidence of cytokeratin-20 and tissue invasion. In general, decreased cytokeratin-20 and cytokeratin-7 are associated with decreased tissue differentiation and increased lymph node involvement.